Management of technological projects and economic profitability in the financial risk of banking institutions (Research, Society and Development, 2022)
This article analyzes the relationship between technology project management (GPT and economic profitability (RE) for the areas of financial risks with the aim of presenting a flexible model between both variables derived from performance indices and cognitive skills for the area of financial risks of a Mexican banking institution. This is through a quantitative method supported by a predictive econometric model of data obtained from 313 technological projects.  The results show that the RE depends on the behavior of the dimensions of the GPT; considering the information taken for empirical verification based on the resulting sample and other data derived from the qualitative indicators.